2019
DOI: 10.1177/0047239519859857
|View full text |Cite
|
Sign up to set email alerts
|

Studying Affective Tutoring Systems for Mathematical Concepts

Abstract: Students face difficulties in learning mathematical processes. As a result, they have negative emotions toward mathematics. The use of technology is employed to change the student’s attitude toward mathematics. Some methods utilize intelligent tutoring systems to recognize student’s emotional state and adapt the learning process accordingly. These systems, known as affective tutoring systems (ATSs), sense the emotional state of a student and then intelligently attempt to suggest appropriate strategies that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Related studies have reported that the effective use of ATS can increase learning motivation and improve learning outcomes ( Moridis and Economides, 2008 ; Sarrafzadeh et al, 2008 ; Lin et al, 2014 , 2020 ; Moga et al, 2014 ; Daouas and Lejmi, 2018 ; Sionti et al, 2018 ; Wang and Lin, 2018 ; Hasan et al, 2020 ). Previous studies have examined the influence of ATS on learning performance during remedial accounting instruction ( Sionti et al, 2018 ) and mathematics ( Mastorodimos and Chatzichristofis, 2019 ). ATS can attract attention, motivate learners, and significantly improve learning performance ( Lin et al, 2014 ; Mehdi et al, 2015 ; Wang and Lin, 2018 ; Bakeer and Abu-Naser, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Related studies have reported that the effective use of ATS can increase learning motivation and improve learning outcomes ( Moridis and Economides, 2008 ; Sarrafzadeh et al, 2008 ; Lin et al, 2014 , 2020 ; Moga et al, 2014 ; Daouas and Lejmi, 2018 ; Sionti et al, 2018 ; Wang and Lin, 2018 ; Hasan et al, 2020 ). Previous studies have examined the influence of ATS on learning performance during remedial accounting instruction ( Sionti et al, 2018 ) and mathematics ( Mastorodimos and Chatzichristofis, 2019 ). ATS can attract attention, motivate learners, and significantly improve learning performance ( Lin et al, 2014 ; Mehdi et al, 2015 ; Wang and Lin, 2018 ; Bakeer and Abu-Naser, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the user can increase the efficiency of learning through interaction with the intelligent agent, and the more the agent's compassionate and encouraging sentences can be used the more the mental state of the person remains positive and can cope with continuous learning. The function of intelligent agents can affect students' learning emotions and can guide learning as well as detect students' learning conditions [10,11]. An Affective Tutoring System (ATS) is a system that can provide users with appropriate teaching content through computer calculations and analysis and can directly give users instant feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Through computer analysis, intelligent tutoring systems (ITS) let subjects learn in individualized courses and provide feedback to users immediately [6]. Much research related to emotional tutoring systems has indicated that system interfaces had positive emotional relevance to learners and could improve learning effectiveness [8][9][10][11]23].…”
Section: Emotional Tutoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Good tutoring requires adequate interpersonal and pedagogical skills, so it is recommended that tutors recognize the emotional state of students and adapt learning processes [11]. In addition to developing a better understanding of students on how to use tutor support [12]; since personal tutoring contributes in creating an environment that supports and facilitates student resilience [13].…”
Section: Research Articlementioning
confidence: 99%